Intermediate Algebra (12th Edition)

Published by Pearson
ISBN 10: 0321969359
ISBN 13: 978-0-32196-935-4

Chapter 4 - Section 4.1 - Integer Exponents and Scientific Notation - 4.1 Exercises: 113

Answer

$\frac{1}{k^{2}}$

Work Step by Step

According to the power rule for exponents, $(a^{m})^{n}=a^{mn}$ (where $m$ and $n$ are integers and $a$ is a real number). Therefore, $(k^{2})^{-3}k^{4}=k^{2\times-3}k^{4}=k^{-6}k^{4}$. According to the product rule for exponents, $a^{m}\times a^{n}=a^{m+n}$. Therefore, $k^{-6}k^{4}=k^{-6+4}=k^{-2}$. According to the negative definition for exponents, $a^{-n}=\frac{1}{a^{n}}$ (where $a\ne0$). Therefore, $k^{-2}=\frac{1}{k^{2}}$.
Update this answer!

You can help us out by revising, improving and updating this answer.

Update this answer

After you claim an answer you’ll have 24 hours to send in a draft. An editor will review the submission and either publish your submission or provide feedback.